Caracterização e confecção de briquetes de casca de liquri (Syagrus coronata (Mart) Becc.) para produção de energia - Scalet, Verônica (2015)
The Licuri bark is a potential source of biomass for energy production. This study aims at making briquettes and the physicochemical characterization of Licuri bark aiming to expand its use as fuel. The material was collected in Great Cauldron - BA and briquettes were made with five different compositions: 100% Licuri bark (T1), 75% Licuri bark + 25% sugar cane straw (T2), 50% Licuri bark + 50% sugar cane straw (T3), 25% Licuri bark + 75% sugar cane straw (T4) and finally 100% sugar cane straw (T5). The briquettes were measured to obtain the value of its expansion and density, passed through drumming test and was made mechanical test on the tensile strength by diametrical compression. Also were made the following analyzes to Licuri bark: moisture content, density, particle size, ash and volatile content, fixed carbon, high heat value, extraction with hot water and cyclohexane / ethanol, lignin and thermogravimetry analysis. Statistical analyzes were made when appropriate (ANOVA and Tukey's test). The expansion of briquettes stabilized after 24 hours of its confection, about the expansion in height, there was no significant difference between treatments, as for the expansion in diameter treatments with the highest percentage of Licuri bark (T1 and T2) showed the lowest expansion. Finally, for the mechanical test the T1 and T2 differed from the other treatments with larger maximum force (34.09 and 34.64 kgf respectively). The moisture content observed was 11.15% ± 1.31, suitable for energy use. The gross calorific value (4652 Kcal.Kg-1 ± 18), the ash content (3.90% + 1.42) and lignin content (36.86 ± 2.6%) of the observed material are high when compared to other biomass. Therefore, the use of Licuri in order to produce energy can be very important for families living of their extraction, because it has favorable characteristics for such use. Moreover, the production of briquettes may optimize the transport process and the burning of the material.